Quality of Life for Elderly Residents in Nursing Homes - Farzianpour, Fereshteh (Glob J Health Sci, 2016)
BACKGROUND AND OBJECTIVES: More than 8% of Iran's populations are elderly. The greatest challenge in this generation is improvement of health and QoL. The main goal of this study was QoL for elderly residents in nursing homes over 65 years in Golestan Province - Iran. METHODS: This research was an analytical cross study. The population society includes the elderly over 65 years in Golestan Province - Iran. The sample size was calculated based on the correlation of 193 elderly men and women. Therefore, if the correlation is 2.0 or greater is statistically significant at 80% and 0.95 confidence. The needed data collected from two questionnaires Consumer product Safety Commission (CPSC) to assess the QOL of nursing homes and the SF-36 for health QOL the elderly indicators through interviews and observation. The reliability of the CPSC questionnaire was estimated using Cronbach's alpha with a coefficient of 0.838. The SF-36 questionnaire was validated with Cronbach's alpha with a coefficient of 0.95. To analyze data, ANOVA one-way test was used that after investigating homogenization of variances with Levin statistic, if homogenization reported P is rejected, the independent T-test was used to interpret it. RESULTS: Among QOL dimensions only General Health (GH) status showed a significant association with supporting organizations covering status (P = 0.01). The relationship between QOL with marital status in both genders was observed that the General Health (GH) (P = 0.001), Physical Functioning (PF) P = (0.007) Mobility Restricts (MR) P = (0.002), Emotional Problems (EP) (P = 0.001), vitality (V) (P = 0.001), Mental Health (MH) (P = 0.001) were significantly related. CONCLUSIONS: There was a significant relationship between the Physical Functioning (PF) mean and the mean of other QOL indicators in two groups of male and female (P = 0.007), also the safety of nursing homes just related respectively with residence variable (P = 0.01) and their employment (P = 0.031).